Growth of invasive pink salmon (Oncorhynchus gorbuscha) at sea assessed by scale analysis - Paulsen, Tora; Sandlund, Odd Terje; Østborg, Gunnel Marie; Thorstad, Eva Bonsak; Fiske, Peder; Muladal, Rune; Tronstad, Stig (Journal of Fish Biology, 2021)
Invasive pink salmon (Oncorhynchus gorbuscha) has been present in variable, but low, numbers in Norwegian waters since c. 1960, but beginning in 2017 their numbers have exploded in rivers in northern Norway, with considerable numbers also recorded in rivers in southern Norway and other countries bordering the North Atlantic. Analysis of pink salmon scales from two rivers draining to the western Barents Sea showed declining growth during the first weeks after entering the sea, and some individuals even showed a pronounced growth arrest, based on detailed scale circulus analyses. This was followed by a period of growth increase and stability during late summer and autumn, which may reflect a transition to better food sources, as the fish migrate from coastal waters to the open ocean, and as they grow larger and can eat larger and more energy efficient food items. Growth declined to a minimum during winter. Fish body size at spawning was positively correlated with the distance from scale focus to the last winter circulus, as well as with the number of circuli. When dividing scale growth into three periods, better growth during the first period at sea was related to increased fish body length at spawning, but this early growth explained only a minor part (6%) of the variation in final body length. The reason for this may be large individual variation in growth combined with large mortality during the first weeks at sea. If mortality is selective, removing fish with poor growth may reduce a correlation between early growth and body size at spawning. Scale growth during late summer and early autumn explained more of the variation in fish length at spawning (27%). Hence, late summer and early autumn was likely an important period for marine growth and survival in the invasive pink salmon.